Chemiluminescence of Rats’ Whole Blood after X-ray and γ-irradiation - A. E. Zaqaryan; H. G. Badalyan
The effects of X-ray and γ-radiations on H2O2-chemiluminescence of rats’ whole blood were investigated. It was found out that when cells and biomaterials were exposed by X-ray radiation an intensification of oxidative processes took place leading to the free radical reactions increase, which is reflected in rise of the level of chemiluminescence (CL). However, by γ-irradiation in small doses the level of CL is slightly increases and at a relatively high dose intensity of H2O2-chemiluminescence decreases, which in our opinion is due to degradation processes, which takes place in biomaterials.
Keywords: Physics; Cross-Disciplinary